The use of graphene for dental polymethylmethacrylate reinforcement - A systematic review - Helena Salgado; Patrícia Fonseca; Mário Vaz; Maria Helena Figueiral; Pedro Mesquita (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
Objectives: To produce a systematic review regarding the effect of graphene-reinforced polymethylmethacrylate used in dentistry on mechanical properties. Methods: Electronic databases (Pubmed/MEDLINE, Web of Science, Embase) were independently searched by two researchers for relevant studies published up to December 2021. An additional manual search was performed to identify relevant publications. The population, intervention, comparison, and outcome (PICO) question was "In dentistry, does graphene-reinforced polymethylmethacrylate offer better mechanical properties than conventional polymethylmethacrylate?". The selection of articles was carried out according to the established inclusion and exclusion criteria, following the PRISMA flowchart. The inter-investigator reliability was assessed by Cohen's Kappa coefficient. The risk of bias was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Quasi-experimental Studies. Results: Six in vitro studies were included in the qualitative analysis. A total of 247 specimens were evaluated: 81 made of non-reinforced PMMA resin and 166 of PMMA reinforced with graphene. The mechanical properties evaluated were flexural strength, flexural modulus, hardness, biaxial flexural strength, and impact strength. These properties seem to improve with the addition of graphene in certain concentrations. The analysis of the risk of bias showed low risk. Conclusions: Within the limitation of this study, graphene seems to strengthen some mechanical properties of PMMA dental resin. However, more studies are needed to understand the ideal graphene concentration to improve resin's clinical performance.